Perancangan Website Sebagai Media Promosi Digital Pada Umkm Ampar Pisang Mengno - Nabilatul Hawa; Septa Amelia; Suci Anggraini; Sularno .; Novadilastri . (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize websites as promotional media to expand their market reach. However, Ampar Pisang Mengno MSME, located in Matur District, Agam Regency, has relied on conventional promotion since its establishment in 2004, limiting product information to local customers. This study aims to design a website as a digital promotional medium to improve information dissemination and support business development. This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The website was developed using the SITE123 platform and includes a homepage, product information, photo gallery, customer testimonials, contact information, location map, and a responsive design. The results indicate that the website provides more comprehensive product information, enhances the business's digital visibility, and strengthens consumer trust. Therefore, the website serves as an effective promotional medium while supporting the digital transformation of rural MSMEs.